Health Costs and Quality of Life Among Diabetic Foot Ulcer Patients: A Cross-Sectional Study - Tauseef Raza, Sana Rehman Joya, Nasir Naseem Akhtar, Muhammad Azhar Qureshi, Muhammad Zafar, Ihsanullah Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetic foot ulcers (DFUs) represent a major condition that emerges from diabetes mellitus and causes various patient health problems together with decreased quality of life and heavy financial burdens on healthcare systems. Objective: The primary objective of this study is to assess the health costs and QoL of patients with DFUs and to explore the correlation between these two factors. Methodology: This cross-sectional study was conducted at KMU Institute of Medical Sciences Kohat during January 2022 to February 2023. A total of 245 patients diagnosed with DFUs were included in the study. Data were collected using validated tools, including the EQ-5D-5L questionnaire to measure QoL and patient records to analyze healthcare expenditures. The health costs were assessed by documenting direct medical costs (consultations, medications, hospitalizations, and wound care) and indirect costs (work absenteeism and caregiver burden). Results: Among 245 patients, Wagner Grade 2 ulcers (28.6%) were most common. Peripheral neuropathy (75.5%) and infections (85.7%) were frequent complications. Health-Related Quality of Life (HRQoL) scores declined significantly with ulcer severity and age, from 55.0 in Grade 0 ulcers to 26.8 in Grade 5 ulcers. Peripheral neuropathy was the most common complication, affecting 75.5% (185 participants) with an average diagnosis time of 10.2 weeks. Infections were present in 85.7% (210 participants), with an average time to diagnosis of 6.4 weeks. Peripheral arterial disease occurred in 44.9% (110 participants), and gangrene in 28.6% (70 participants). Conclusion: DFUs impose a dual burden of high healthcare costs and diminished QoL, necessitating cost-effective, multidisciplinary management strategies. Keyword: Quality of Life, Health Cost, Diabetic Foot Ulcer